Treatment Of Textile Wastewater Using Bio-Char Based Palm Oil Mill Sludge (POMS) - Thibashini, Selvam (2022)
The aim of this research is to prepare activated biochar, a value added product from waste the by-product means sludge produced from palm oil mill sludge (POMS) through chemical activation. Biochar has been used in a variety of applications since its discovery as a solid and effective adsorbent. It is widely used to extract odour and certain heavy metals from sewage, drainage, and leachate, it is also inexpensive and widely available in the marketplace. With its highly micro porous structure, it is reliable and effective for extracting contaminants from aqueous solutions. The sludge generated as by product of this process is recovered and converted into activated biochar. POMS sludge was used as main precursor to prepare the biochar. The physical properties of biochar are determined by the activation mechanism and process parameters. The sludge preparation process followed by drying and pyrolysis with the absence of oxygen, drying procedure was first conducted in an oven at 105°C for 24 hours to turn the (POMS) into a highly carbonaceous substance. The biochar formed is activated using acid and alkaline reagent to generate chemically activated biochar with a high porosity and effectiveness. Then, the activated biochar is undergone pyrolysis process at different temperature as 500°C, 600°C and 700°C for 60 minutes. The surface properties and elemental compositions of the biochar obtained as characterised. By combining the adsorbent and wastewater in a conical flask and shaking it at 200 rpm for 10 minutes, the POMS based biochar was used to treat textile dye wastewater. The research finding the activation of biochar based (palm oil mill sludge) could be used as an adsorbent candidate for treating chemical oxygen demand (COD), colour, pH from textile wastewater.